BiOBr/Bi2S3 heterojunction with S-scheme structureand oxygen defects: In-situ construction and photocatalytic behavior for reduction of CO2 with H2O - Miao, Zerui; Zhang, Yanfeng; Wang, Ning; Xu, Peng; Wang, Xuxu (Journal of colloid and interface science, 2022)
[Display omitted] Constructing heterojunction has been considered as an efficient strategy to promote the separation and transfer of photogenerated carriers and improve redox ability of single photocatalyst. Herein, S-scheme BiOBr/Bi2S3 heterojunction with surface oxygen vacancies (OVs) was synthesized in situ by a facile hydrothermal method. The as-prepared photocatalyst show high activity for CO2 photoreduction with pure water. The yields of product CO and CH4 are as high as 100.8 and 8.5 µmol g−1h−1, which are 17.5 and 13.5 times higher than that of the pristine Bi2S3, and 2.3 and 4.7 times higher than that of the pristine BiOBr respectively. The excellent activity of the BiOBr/Bi2S3 heterojunction is attributed to both the S-scheme electron structure and the surface OVs of the component BiOBr. The S-scheme structure can enhance utilization of sunlight and improve the separation and transfer of photogenerated electron/hole pairs. The surface OVs of BiOBr can serve as active sites of CO2 and H2O in the photocatalytic process. This work provides some novel insights of S-scheme heterojunction with defects for photocatalytic CO2 reduction.